2010
DOI: 10.1253/circj.cj-10-0376
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Collateral Growth and Its Therapeutic Application to Coronary Artery Disease

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp or a long time, the functional role of the coronary collateral circulation as a blood-conveying channel has been disputed. 1-4 Because a well-developed coronary collateral circulation is usually associated with severe coronary stenosis, some investigators assumed that the existence of collateral circulation is a marker of coronary artery disease (CAD). 1 Over the past 3 decades, accumulating evidence has documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…3 Several investigators have reported that vascular alterations in coronary, skeletal muscle, or intestinal vasculature can be induced by training. [14][15][16][17][18] It has been proposed that this trainingrelated vascular adaptation is a complex process that is strongly dependent on the size and tissue location of the vessel. In other words, exercise training may trigger different adaptation mediators in different tissues that contain vessels of different sizes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several investigators have reported that vascular alterations in coronary, skeletal muscle, or intestinal vasculature can be induced by training. [14][15][16][17][18] It has been proposed that this trainingrelated vascular adaptation is a complex process that is strongly dependent on the size and tissue location of the vessel. In other words, exercise training may trigger different adaptation mediators in different tissues that contain vessels of different sizes.…”
Section: Discussionmentioning
confidence: 99%
“…1 These neovessels play an important role in plaque development and progression. [2][3][4][5][6] Initially, neovascularization is induced by hypoxia and ongoing inflammatory reaction in the atherosclerotic area. Both hypoxia and inflammation activate in turn various angiogenic factors (eg, hypoxia-inducible growth factor, vascular endothelial growth factor (VEGF), fibroblast growth factor, platelet-derived growth factor (PDGF), angiopoietins (Ang), ephrins, and others).…”
mentioning
confidence: 99%
“…The literature is replete with the salubrious efects of a well-developed coronary collateral circulation and the potential beneit of a therapeutic process aimed at stimulating coronary collateral growth [13][14][15][16][17][18][19]. One patient study focused on coronary collateral growth in patients that had stable coronary artery disease.…”
Section: Methodsmentioning
confidence: 99%